The effect of inter-repetition rest duration on kinematic of snatch - Tan, K.; Mohamad, N. I. B.; Nadzalan, A. M. (Annals of Applied Sport Science, 2021)
Background. Controlling and manipulating inter-repetition rest (IRR) could develop diverse levels of fatigue and manifest changes to lifting mechanics. Objectives. This study's objective was to examine the effect of IRR on the kinematic of snatch lifting during multiple set exercise protocol. Methods. Fifteen male (n=15) athletes participated in this study (age = 21.0 ± 1.41 years; body weight = 60.82 ± 2.45 kg; height = 165.70 ± 10.88 cm; snatch one-repetition maximum (1RM)/body mass = 0.73 ± 0.117). Session 1 consisted of anthropometric and 1RM determination. Sessions 2-4 involved subjects performing three sets x 5 repetitions of 85% 1RM with 10, 30, or 50 seconds of IRR implemented randomly. Ankle, knee, and hip joint velocity and barbell velocity (BV) were obtained during each protocol using VICON Motion Analysis (100Hz). Results. Repeated measure ANOVA showed significant differences found in ankle, knee, and hip joint velocity. The barbell velocity showed a significant effect between IRR, (F (2, 28) = 22.831, P < 0.05). Repeated measure Manova showed a significant effect of IRR on the maintenance of kinematics variables across repetition. Barbell velocity showed a significant effect of IRR on the maintenance of velocity across repetition (P = 0.029). Conclusion. Due to the differences found between IRR protocols, the implementation of IRR may increase or decrease kinematic output due to the different levels of fatigue. The implementation of IRR can help to maintain kinematic variables, which often are affected by neuromuscular fatigue occurred with continuous repetition.